Quantum Relativistic Diesel Engine with Single Massless Fermion in 1 Dimensional Box System - Setyo, Deny Pra; Latifah, Eny; Hidayat, Arif; Wisodo, Hari (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2018)
The quantum Diesel of a single fermion in 1D box system has been explored. The Fermion particle meets the Dirac's relativistic Hamiltonian with a chosen mass worth zero. This Relativistic Diesel engine research aims to obtain Diesel engine efficiency that utilizes massless fermion particles as a working substance. This study implements a modified analogy model of the classical analogue model to quantum with the implementation of the first law of thermodynamics for quantum systems so that quantum thermodynamic processes can be defined explicitly. The exploratory results of a single quantum fermion Diesel engine of a single massless system are efficiency formulation that is suitable for the efficiency of a classic Diesel engine, but its heat capacity ratio is unique, that is 2. Based on the value of heat capacity ratio, the efficiency is higher than the classical.